Regulation of drug transporter expression and function in the placenta - Staud, Frantisek; Ceckova, Martina (Expert opinion on drug metabolism & toxicology, 2015)
INTRODUCTION: Medication of pregnant women is increasingly common in developed countries. Several placental drug transporters have been shown to transfer their substrates from the trophoblast back to the maternal circulation, thus hindering the transplacental passage of xenobiotics and protecting the fetus. However, the expression and activity of drug transporter proteins in the placenta vary during gestation and are tightly regulated by many factors. In addition, their function can be compromised by pathological conditions and/or drug-drug interactions. AREAS COVERED: This article reviews current knowledge on placental drug transporters, their effects on placental pharmacokinetics and the regulatory mechanisms that control their expression and activity. Transcriptional, genetic and epigenetic mechanisms of placental transporter regulation and the drug-drug interactions that modulate transporter activity are described. Physiological and pathological factors that can affect drug transporter expression and function in the placenta are also discussed. EXPERT OPINION: The expression and activity of drug transporter proteins in the placenta vary during gestation and are tightly regulated by many factors. Subsequently, there is a great variability in the expression and function of placental drug transporters both within human populations (interindividual variability) and also during gestation (intraindividual variability). An understanding of the expression and function of placental drug transporters is essential for efficient and safe therapy during pregnancy. There is clearly a need for further preclinical and clinical studies on placental drug transporters, but such investigations must be carefully designed and the resulting data should be evaluated with great caution. This review highlights several methodological aspects that will have to be considered and addressed in order to shed further light on these important issues.
Keywords: maternofetální výměna látek; membránové transportní proteiny; drug transporter; pharmacotherapy; Pregnancy; Humans; regulation; lékové interakce; Placenta; Female; genetics; pharmacokinetics; lidé; Membrane Transport Proteins; zvířata; Xenobiotics; Drug Interactions; epigenetics; biologický transport; ženské pohlaví; pregnancy; těhotenství; xenobiotika; gestation; Animals; Maternal-Fetal Exchange; placenta; expression; Biological Transport